Potassium Inwardly Rectifying Channel Subfamily J Member 11 (KCNJ11) RS5219 Gene Polymorphism as a Risk Factor for Type 2 Diabetes Mellitus in Indonesia: A Case Control Study - Putri, Annisa Septiani Putri; Pratamawati, Tiar Masykuroh; Nauphar, Donny (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Diabetes Mellitus (DM) is a chronic metabolic disease caused by the failure of the pancreas to produce the hormone insulin or ineffective use of the hormone insulin. It is estimated that 537 million adults aged 20-79 years worldwide suffer from DM. Genetics is one of the risk factors involved in the pathophysiology of type 2 DM. The KCNJ11 gene encodes the Kir6.2 protein that is responsible for adenosine triphosphate-sensitive potassium ion channels (kATP) synthesis in pancreatic beta cells plasma membrane. Aims: This study aims to examine the KCNJ11 rs5219 gene polymorphism as a risk factor for type 2 diabetes mellitus in Cirebon population. Methods: This case control study involved 29 cases of type 2 diabetes mellitus and 29 healthy controls with purposive sampling technique. Sample data was obtained through the examination of blood sugar, DNA extraction, PCR-RFLP with Eco24I restriction enzyme, then visualization of the results with Gel Electrophoresis. Results: The frequency of G allele was found more in the case group (70%) while the frequency of A allele was found more in the control group (38%). The frequency of heterozygous GA genotype was found more in the control group (48.3%) and the frequency of homozygous mutant AA genotype was more in the case group (17.2%) compared to the control group (13.8%). Chi-Square Test results obtained p-value 0.115, OR value 2.318. Conclusion: This study showed no significant association between Potassium Inwardly Rectifying Channel Subfamily J Member 11 (KCNJ11) rs5219 gene polymorphism and the incidence of Type 2 Diabetes Mellitus in Cirebon population.